A serological investigation in Southern Italy: was SARS-CoV-2 circulating in late 2019?. Issue 5 (30th November 2022) - Trombetta, Claudia Maria; Marchi, Serena; Viviani, Simonetta; Manenti, Alessandro; Casa, Elisa; Dapporto, Francesca; Remarque, Edmond J.; Bollati, Valentina; Manini, Ilaria; Lazzeri, Giacomo; Montomoli, Emanuele
ABSTRACT: In March 2020, the first pandemic caused by a coronavirus was declared by the World Health Organization. Italy was one of the first and most severely affected countries, particularly the northern part of the country. The latest evidence suggests that the virus could have been circulating, at least in Italy, before the first autochthonous SARS-COV-2 case was detected in February 2020. The present study aimed to investigate the presence of antibodies against SARS-CoV-2 in human serum samples collected in the last months of 2019 (September–December) in the Apulia region, Southern Italy. Eight of 455 samples tested proved positive on in-house receptor-binding-domain-based ELISA. Given the month of collection of the positive samples, these findings may indicate early circulation of SARS-CoV-2 in Apulia region in the autumn of 2019. However, it cannot be completely ruled out that the observed sero-reactivity could be an unknown antigen specificity in another virus to which subjects were exposed containing an epitope adventitiously cross-reactive with an epitope of SARS-CoV-2.